Web-Based Village Information System in Dalegan Village – Panceng District - Gresik Regency - Pandu Setiaji; Langgra Mayrezka Pradipta; Agus Budhi Utomo (OJS Universitas Muhammadiyah Gresik, 2019)
The development of information technology has made the internet as a very important requirement to explore various information needed. The benefits of the internet are quite large especially in the world of business, entertainment and education. Dalegan Village is a village that has a lot of natural wealth such as white sand beach tourism, hill prohibit, legen drinks, fish crackers and various other fish preparations, but all these riches have not been fully exposed in cyberspace. This program aims to build a web-based village information system to expose the history and profile of the village and optimize the existence of the natural wealth of the village of Dalegan so that information about the natural wealth can be conveyed to all internet users so that it can increase the interest of tourists who wilvisit and increase the budget of the village income.